Restorative Justice Principles in Law Enforcement and Democracy in Indonesia (Journal of Indonesian Legal Studies, 2022)
Indonesian legal system has not yet adopted the concept and method of restorative justice; therefore, substantial justice for the Indonesian people has not yet been reflected in legal enforcement in the Pancasila democracy system. The research aims to elaborate on the existence of restorative justice in the criminal justice system, which supports the process of democracy in Indonesia. Normative research is used to establish the aim of the research by using secondary data and primary, secondary, and tertiary legal resources. The urgency of this article is to capture how the legal enforcer is using restorative justice. The findings and conclusion of the research determined that restorative justice is based on legal and cultural values in the society, which gave a conventional resolution that fulfils justice. The application of restorative justice is constructed through standard procedures based on the system theory approach, which accommodates all roles and functions of the criminal justice system elements. Therefore, legitimacy, legality, responsibility, and supervision are warranted philosophically, juridically, and sociologically. As a result, implementing the concept of restorative justice in the criminal justice system is a choice for the strategy in politics of law. Restorative justice will support the law enforcement in Indonesia as required in order to create democracy in Indonesia based on Pancasila and Constitution of 1945.